2010
DOI: 10.1007/s10165-010-0346-y
|View full text |Cite
|
Sign up to set email alerts
|

The short-term outcome of the modified Sauvé–Kapandji procedure regarding range of motion, carpal bone translation and bony shelf size

Abstract: The Sauvé-Kapandji (S-K) procedure is a common treatment for rheumatoid wrists, but in some cases severe bone destruction makes this operative modality difficult to perform, while also resulting in a poor outcome. A modified S-K procedure for these wrists has been reported, but the clinical outcomes of the modified procedure are unclear. This study evaluated 24 wrists in 20 patients who underwent the modified S-K procedure. The mean follow-up period was 34.5 months. The clinical assessments were range of motio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Our findings in the present study are consistent with previously reported data. [1][2][3][4][5][6][7][8][9] As described previously, there are two possible reasons for the postoperative decrease in wrist flexion. The most probable reason is dorsal soft tissue contracture caused by intra-articular invasion.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Our findings in the present study are consistent with previously reported data. [1][2][3][4][5][6][7][8][9] As described previously, there are two possible reasons for the postoperative decrease in wrist flexion. The most probable reason is dorsal soft tissue contracture caused by intra-articular invasion.…”
Section: Discussionmentioning
confidence: 92%
“…Many previous studies on the S-K procedure with extensor tendon repair evaluated the pre-and postoperative ROM of the wrist. [1][2][3][4][5][6][7] Most of the reports showed that ROM of wrist flexion decreases postoperatively, [1][2][3][4][5] whereas some of the reports showed a significant decrease. 6,7 To our knowledge, two previous studies evaluated ROM in the S-K procedure without extensor tendon rupture in OA patients and little is known about those in RA patients (►Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations